Non-Additivity of Subjective Expectations over Different Time Intervals - Peter Haan; Chen Sun; Uwe Sunde; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We examine the additivity of stock-market expectations over different time intervals. When asked about a ten-year interval, survey respondents expect a stock-price change that is not equal to, but closer to zero than, the sum of their expectations over two shorter time intervals that cover the same ten years. Such sub-additivity is irrational in that it cannot stem from aggregating short-term expectations. Model estimates show that the pattern is consistent with a time perception where shorter time intervals have a proportionally larger weight. We also find that the respondents' degree of additivity is correlated with making larger financial investments.
Keywords: D01; D14; D84; D09; 330; expectation formation; time perception; sub-additivity; super-additivity